Is LCC relevant in a sustainability assessment?. - Klopffer, Walter
In a recent letter to the editor, Jorgensen et al. questioned that life cycle costing (LCC) is relevant in life cycle based sustainability assessment (LCSA). They hold the opinion that environmental and social aspects are sufficient. We argue that sustainability has three dimensions : environment, economy, and social aspects in accordance with the well accepted "three pillar interpretation" of sustainability, although this is not verbally stated in the Brundtland report (WCED 1987). An analysis of the historical development of the term "sustainability" shows that the economic and social component have been present from the beginning and conclude that LCSA of product systems can be approximated by LCSA = (environmental) LCA + (environmental) LCC + S-LCA where S-LCA stands for social LCA. The "environmental" LCC is fully compatible with life cycle assessment (LCA), the internationally standardized (ISO 14040 + 14044) method for environmental product assessment. For LCC, a SETAC "Code of Practice" is now available and guidelines for S-LCA have bee published by UNEP/SETAC. First examples for the use of these guidelines have been published. An important practical argument for using LCC from the customers' point of view is that environmentally preferable products often have higher purchasing costs, whereas the LCC may be much lower (examples : energy saving light bulbs, low energy houses, and cars). Also, since LCC allows an assessment for different actor perspectives, the producers may try to keep the total costs from their perspective below those of a conventional product : otherwise, it will not succeed at the market, unless highly subsidized. Those are practical aspects which finally decide about success or failure of "sustainable" products. Whether or not an analysis using all three aspects is necessary will depend on the exact question. However, if real money flows are important in sustainability analysis of product systems, inclusion of LCC is advisable.
Keywords: Life cycle costing; Social life cycle assessment; Sustainability assessment